If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23x = 3(8x + 6) Reorder the terms: 23x = 3(6 + 8x) 23x = (6 * 3 + 8x * 3) 23x = (18 + 24x) Solving 23x = 18 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. 23x + -24x = 18 + 24x + -24x Combine like terms: 23x + -24x = -1x -1x = 18 + 24x + -24x Combine like terms: 24x + -24x = 0 -1x = 18 + 0 -1x = 18 Divide each side by '-1'. x = -18 Simplifying x = -18
| 6a-2B=20 | | -8n+20=124 | | 58-(55-2)=x | | 3x-25=2x+115 | | 72-18=x | | K^2-15k-54=0 | | 4n^2-10=0 | | 2(36-9)=x | | Ln-3x=-1 | | 4600/8000000 | | 75-18=x | | 4r+5=2r+11 | | 3a^2-9=11 | | 2x+10+x+(3x-16)=90 | | 4r-1=2 | | 4x-1/5x | | 2x+6+2x+(4x-8)=62 | | 13*(9-6)=n | | Y=4/9x-3 | | 5u-6+5(2u+3)=-3(u+1) | | 7(2x-3)=3(3x-11) | | 4xsquared=144 | | z-4+9=6 | | -1.476-1.6a=3.6a-0.28 | | z-4+ 9= 6 | | s^2+20s-17=0 | | u^2-28u=-15 | | 23.18+5.8= | | lnx^7-5lnx-2=0 | | y=3x^2+5x-300 | | y^2+2y-11=0 | | 2x(x-1)+3(x-1)=0 |